DOMESTICATION OF CULTURAL WORDS TRANSLATION IN MALALA YOUSAFZAI'S AUTOBIOGRAPHY ENTITLED "I AM MALALA: THE GIRL WHO STOOD UP FOR EDUCATION AND WAS SHOT BY THE TALIBAN" - Khairunissa, Seila (2015)
The study is aimed at examining the domestication strategies which were used in translating cultural words in Malala Yousafzai's autobiography entitled I Am Malala: The Girl who Stood Up For Education and was Shot by the Taliban. One hundred and forty five cultural words were collected from the translated version of the book by employing non-probability sampling method. A qualitative method was applied in this study in order to answer the formulated research questions; namely (1) what categories of cultural words are found in the book and (2) what strategies of domestication which were applied in translating the cultural words in the book. The one hundred and forty five cultural words were categorized based on Tomalin and Stempleski's (1993) categorization of cultural words and identified based on the domestication strategies proposed by Venuti (1995). The study found that products (49%) was the categorization of cultural word which appeared most frequently, followed by ideas (42%) and behaviors (10%). Five out of six domestication strategies were applied by the translator in translating the cultural words. One hundred and six cultural words were translated into bahasa Indonesia by using equivalent translation. The domination of equivalent translation as the domestication strategy which was mostly applied is due to the fact that some source language features have been converted in the target language as the translator effectively translated the source language cultural words into the words which carried the equal meaning in the target language. In the process of translating the book, it is considered that the domestication strategy is considered appropriate to represent most of the source language cultural words in the studied book. The domestication strategy effectively represents the message of the source language transparence in the translation text so that the receptor language could possibly obtain the similar message contained in the original text. In addition, domestication strategy also produces translation text which is easy to be understood by the target readers. Penelitian ini bertujuan untuk mengamati strategi-strategi domestication yang digunakan dalam penerjemahan kata kultural dari autobiografi Malala Yousafzai yang berjudul I Am Malala: Menantang Maut di Perbatasan Pakistan-Afghanistan. Seratus empat puluh lima kata kultural dikumpulkan dari versi terjemahan dengan menggunakan metode sampling non-probabilitas. Sebuah pendekatan kualitatif digunakan dalam penelitian ini untuk menjawab pertanyaan-pertanyaan yang telah dirumuskan; yaitu (1) kategori kata kultural apa saja yang ditemukan dalam buku dan (2) strategi-strategi domestication apa yang digunakan oleh pengalih bahasa dalam menerjemahkan kata kultural yang terdapat di dalam buku. Seratus empat puluh lima kata kultural yang telah dikumpulkan dikategorisasikan berdasarkan kategorisasi kata kultural yang diusulkan oleh Tomalin and Stempleski (1993) dan diidentifikasi berdasarkan strategi-strategi domestication yang diusulkan oleh Venuti (1995). Penelitian ini menemukan bahwa products (49%) merupakan kategorisasi dari kata kultural yang paling banyak muncul, diikuti oleh ideas (42%) dan behaviors (10%). Lima dari enam strategi domestication digunakan oleh pengalih bahasa dalam menerjemahkan kata kultural. Seratus enam kata kultural diterjemahkan ke dalam bahasa Indonesia dengan mengggunakan equivalent translation. Dominasi dari equivalent translation sebagai strategi domestication yang paling sering digunakan merujuk pada fakta beberapa fitur bahasa sumber telah dikonversikan ke dalam bahasa target dikarenakan pengalih bahasa mampu menerjemahkan kata kultural dari bahasa sumber secara efektif serta menemukan kata yang memiliki padanan makna di dalam target bahasa. Dalam proses penerjemahan teks, dipertimbangkan bahwa strategi domestication pantas untuk digunakan dalam menerjemahkan hampir seluruh kata kultural dari bahasa sumber dalam buku yang diteliti. Strategi domestication secara efektif menerjemahkan pesan yang terkandung dalam bahasa sumber secara jelas sehingga bahasa penerima secara memungkinkan dapat menerima pesan yang sama dengan pesan yang terdapat dalam text asli. Selain itu, strategi domestication juga menghasilkan teks terjemahan yang mudah untuk dimengerti oleh para target pembaca.